Equity, well-being and ecosystem health: participatory research for natural resource management - Consultative Group on International Agricultural Research (2000)
A new vision of humanity’s relationship to nature is gathering strength. We are beginning to see our world as a living system, in which we ourselves are embedded. And we are gaining a greater awareness of our dependence on nature’s ecological services and on one other. Our emerging mental map of the world shows it as an integrated whole rather than a collection of parts. Of course, much human behavior suggests otherwise. As a result of our activities, the earth’s forests are receding, while its deserts are expanding. Topsoil is diminishing, and the ozone layer, which protects us from ultraviolet radiation, is being depleted. Concentrations of heat-trapping gases in the atmosphere are rising, while the numbers of plant and animal species are shrinking. The human population continues to expand, as the gap between rich and poor widens. Nonetheless, people in all walks of life are realizing that the major problems of our time are interconnected and that the only viable solutions are those that satisfy today’s needs without diminishing future prospects. We have made a start toward building sustainable communities, in which we can fulfil our own aspirations while leaving a healthy world for tomorrow’s children. To make this vision a reality means creating equitable social and economic arrangements that protect and maintain the ecological services that earth provides--and learning to live within our ecological means. This publication shows how scientists from centers supported by the Consultative Group on International Agricultural Research (CGIAR) are working with farmers, communities, and organizations to improve the health and well-being of people and our environment. Toward this end the various projects described here are developing and practicing innovative participatory approaches for research on natural resource management (NRM). This research deals with such issues as resource monitoring, policy and legal frameworks, participatory learning, collective resource management, and learning communities. The case studies presented in this publication demonstrate the critical role of participatory approaches in NRM research, highlighting the roles of different stakeholders, the significance of scales and time dimensions, the inevitability of tradeoffs, and the challenges of dealing with complexity.